Antimicrobial activity and biofilm inhibition of riparins I, II and III and ultrastructural changes in multidrug-resistant bacteria of medical importance. (December 2020) - Oliveira-Júnior, Jorge Belém; da Silva, Everton Morais; Veras, Dyana Leal; Ribeiro, Karla Raíza Cardoso; de Freitas, Catarina Fernandes; de Lima, Fernanda Cristina Gomes; Gutierrez, Stanley Juan Chavez; Camara, Celso Amorim; Barbosa-Filho, José Maria; Alves, Luiz Carlos; Brayner, Fábio André
Abstract: Natural products have been used to treat various infections; however, the development of antimicrobials has made natural products in disuse. Riparin I, II and III are natural alkamide isolated from Aniba riparia (Ness) Mez (Lauraceae), that exhibit economic importance and it is used in traditional medicine, and popularly known as "louro". This study investigated the cytotoxicity, antimicrobial and antibiofilm activity, and ultrastructural changes in vitro by riparins I, II and III in Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii and Pseudomonas aeruginosa . We analyzed the cytotoxicity by MTT assay in Vero cells and hemolytic action verified in human erythrocytes. The antimicrobial activity was determined by microdilution in broth against ATCC strains, identifying the susceptible species. Subsequently, only the MDR isolates of sensitive bacterial species were evaluated regarding its biofilm formation and ultrastructural changes. Riparin I presented low cytotoxicity and hemolytic percentage ranging from of 9.01%–12.97%. Only the riparin III that showed antimicrobial activity against MDR clinical isolates, and significant reduction in biofilm formation in S. aureus . Moreover, the riparin III promoted ultrastructural changes in bacterial cells, such as elongated cellular without bacterial septum, cells with a rugged appearance on the cell surface and cytoplasmic material extravasation. As has been noted riparin III has an inhibitory potential against biofilm formation in S. aureus, besides having antimicrobial activity and promoting ultrastructural changes in MDR clinical isolates. Thus, riparin III is an interesting alternative for further studies aiming to develop new therapeutic options. Graphical abstract: Image 1 Highlights: Riparin III exhibited antimicrobial activity in MDR S. aureus and A. baumannii. Riparin III showed cytotoxicity of 142  μ g/mL and hemolytic percentage of 12.97%. Riparin III showed inhibition of the formation of S. aureus biofilm. Ultrastructural changes in S. aureus and A. baumannii exposed to riparian III.